Android-Based Interactive Learning Multimedia: Social Studies Material for Fourth Grade Elementary School Students - Gusti Izhar; Anwar Senen; Kristi Wardani; Dita Salsavira Cahaya Ningrum (Universitas Pendidikan Ganesha, 2023)
Today's learning media have yet to facilitate students' involvement in the learning process fully. This study aims to develop and analyze the effectiveness of Android-based interactive learning multimedia on economic activity material and its relationship to various fields of work and social and cultural life in the environment around elementary school students. The development model used is the Borg and Gall model with 10 development steps. The research subjects used 86 students and 4 grade IV elementary school teachers. The trial was conducted twice, and the operational or effectiveness test used a quasi-experimental design with a nonequivalent control-group design. Data was collected using interviews, questionnaires, scales, and tests. The data analysis technique used is qualitative and quantitative using the T-test. The results of this development research show that the developed Android-based interactive learning multimedia meets the eligibility criteria of